2018
DOI: 10.1162/leon_a_01471
|View full text |Cite
|
Sign up to set email alerts
|

Practice-Based Research in the Creative Arts: Foundations and Futures from the Front Line

Abstract: This article explores the subject of practice-based research, its application in the creative arts and its role in generating new forms of knowledge in the context of the PhD. Our aim is to provide more clarity about the nature of practice-based research, the approach we advocate and how it contributes to new knowledge that can be shared and scrutinized in a form that is both accessible and rich in its representation of the full scope of creative arts research. We draw on examples spanning over 35 years of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(79 citation statements)
references
References 1 publication
0
68
0
1
Order By: Relevance
“…These students also have transformative aesthetic experiences that redefine how they perceive natural and human-made phenomena (13)(14)(15)(16). Creative practitioners of today increasingly combine art, design, technology, science, engineering knowledge, and skill in practice-led research processes, known widely as "practice-based research" (17). Some creative practitioners make contributions to scientific and engineering research (18).…”
Section: Overview Of the Eventsmentioning
confidence: 99%
“…These students also have transformative aesthetic experiences that redefine how they perceive natural and human-made phenomena (13)(14)(15)(16). Creative practitioners of today increasingly combine art, design, technology, science, engineering knowledge, and skill in practice-led research processes, known widely as "practice-based research" (17). Some creative practitioners make contributions to scientific and engineering research (18).…”
Section: Overview Of the Eventsmentioning
confidence: 99%
“…Both the scientific and creative fields use experimentation through practice-led processes to test assumptions; during this process new questions might emerge (Candy and Edmonds 2018), which can lead to knowledge production (Borgdorff 2012, 68). Evaluations and judgements are based on previous experience and expertise that grows over time.…”
Section: Experiential Knowledgementioning
confidence: 99%
“…). Within art and design research, practitioners have identified challenges on claiming the validity of artefacts in research due, in part, to the ambiguity surrounding the definition, objective and value of ‘practice‐based research’ (Biggs ; Candy & Edmonds ), as well as what constitutes an ‘artefact’ (Candy & Edmonds ; Rust et al . ).…”
Section: Introductionmentioning
confidence: 99%